1992
DOI: 10.1128/mcb.12.5.2282
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic action of interleukin-6 and glucocorticoids is mediated by the interleukin-6 response element of the rat alpha 2 macroglobulin gene.

Abstract: One class of genes coding for the acute-phase proteins (acute-phase genes) is induced by interleukin 6 (IL-6) through the human transcription factor NF-IL-6 and its rat homolog IL-6-DBP/LAP. A second class, represented by the rat alpha 2 macroglobulin gene, utilizes a different IL-6 response element (IL-6-RE) and different DNA-binding proteins interacting with this element, the so-called IL-6-RE binding proteins (IL-6 RE-BPs). Human Hep3B and HepG2 hepatoma, U266 myeloma, and CESS lymphoblastoid cells contain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
83
0

Year Published

1993
1993
2008
2008

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 141 publications
(88 citation statements)
references
References 47 publications
(66 reference statements)
5
83
0
Order By: Relevance
“…The same band was also seen with the α 2 -macroglobulin-specific probe (data not shown). The bands obtained are similar to the data previously published with a typical IL-6 RE (19). The specificity of the binding was confirmed by competition assays.…”
Section: The Three Il-6 Re In the Entpd2 Promoter Are Bound By Proteisupporting
confidence: 78%
See 1 more Smart Citation
“…The same band was also seen with the α 2 -macroglobulin-specific probe (data not shown). The bands obtained are similar to the data previously published with a typical IL-6 RE (19). The specificity of the binding was confirmed by competition assays.…”
Section: The Three Il-6 Re In the Entpd2 Promoter Are Bound By Proteisupporting
confidence: 78%
“…In this study we have shown that PF express gp130, providing a molecular basis for IL-6 responsiveness. IL-6-sensitive changes in transcription are mediated via actions of specific promoter IL-6 REs (16,19). Although the intermediate steps coupling IL-6 receptor activation and IL-6 REs are unclear, a set of IL-6 RE binding proteins have been identified, which mediate IL-6-sensitive induction of α 2 -macroglobulin (19).…”
Section: Discussionmentioning
confidence: 99%
“…Our analysis also revealed other consensus nucleotide sequence motifs in the metchnikowin promoter, corresponding to mammalian NF-IL6 response elements (Hocke et al, 1992), GATA sites (Orkin, 1992), and interferon consensus response elements (Figure 4(c)). …”
Section: Cloning Of the Metchnikowin Genementioning
confidence: 94%
“…In addition to Rel sites, the metchnikowin promoter contains sequence motifs homologous to cisacting regulatory elements binding the mammalian transcription factors GATA (Orkin, 1992), NF-IL6 (Hocke et al, 1992), as well as several GGAAANN sequence motifs present in the interferon consensus response elements of mammalian interferoninduced genes . In mammals, cooperative interaction of NF-kB with multiple transcription factors is well documented (Siebenlist et al, 1994).…”
Section: Regulation Of Metchnikowin Gene Expressionmentioning
confidence: 99%
“…interleukin-1 (IL-l), IL-6 and tumour necrosis factor-a (TNFa) [6,7& a,-Macroglobulin synthesis is primarily induced by IL-6 and is considerably further enhanced by glucocorticoids in vivo and in vitro [8,9]. The 5' flanking region of the rat a2-macroglobulin gene contains both IL-6 and glucocorticoid response elements [lO,l 11.…”
Section: Introduction 2 Materials and Methodsmentioning
confidence: 99%